Ápice: plan parcial de conexión y rehabilitación eco productivo Sabana Centro (2019)
The project seeks to strengthen the economy at the regional level through the exploitation of flowers as an element and products derived from it, focused on farmers, small businesses and large companies, as well as the themes to be worked on within the project are the theme presentation of flower culture, bio-innovation, technification, sale and export.